A cadeia produtiva do leite no Paraná e sua contribuição no desenvolvimento econômico da microrregião de Toledo - Luz, Joseli Turmina da (2021)
This dissertation analyzed the contribution of the milk production chain in the economic development of the microregion of Toledo from 2006 to 2018. Hirschman's theoretical approach of from the productive chains was used to support the analysis through the indicators of Locational Quotient, Coefficient of Specialization and Coefficient of Restructuring for dairy cattle raising, milk preparation and dairy manufacturing sectors. The results showed that the municipalities of the microregion of Toledo, in the period between 2006 and 2018, underwent important restructuring processes of their economic activities, demonstrating that the dairy activity is part of the economic reality of the microregion, especially for the agro-industrial sector. The activity presented expressive volume in the production and productivity of milk in the microregion compared to the state of Paraná. The highest values of the gross value of production (GVP) of livestock were concentrated in municipalities with a diversified production base and in selected sectors, manufacture such as dairy concentrates the largest number of jobs in the microregion. For the milk GVP, three municipalities had the highest values and the highest amount of milk produced. The milk production chain is responsible for many formal jobs in the analyzed municipalities, generating employment and income, in addition to contributing to the economic development of the microregion of Toledo.